Sitenar: Transformasi pembelajaran matematika berbantuan aplikasi articulate storyline 3 - Agil Dwi Mustika; Euis Eti Rohaeti; Chandra Novtiar (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2026)
This study was motivated by students’ low mathematical communication skills. The research aimed to develop an interactive learning media using Articulate Storyline 3 that is feasible and effective in improving students’ mathematical communication skills through a Problem-Based Learning model. This study used a Research and Development (R&D) method using the ADDIE model. The subjects were tenth-grade students at a vocational high school in West Bandung Regency. Data collection instruments included media expert and material expert validation, mathematical communication skills tests, observation, interviews, and questionnaires. Data analysis techniques consisted of normality test, Wilcoxon test, and Mann-Whitney test. The results showed that product validity reached 98,61% based on material expert validation and 94,44% based on media expert validation, both of which were categorized as highly valid. The practicality level of the product reached of 95,21% on-to-one trial, 81,50% small group trial, and 83,94% field trial, all categorized as highly practical. The effectiveness of the product was indicated by the N-Gain score of 0,76 in the experimental class and 0,49 in the control class. It can be concluded that learning using the SiTenar media is  more interactive and more effective in improving students’ mathematical communication skills compared to conventional learning.